Gambaran Kelengkapan Administrasi dan Farmasetik Resep Rawat Inap di RSU Sumekar Tahun 2022 - Prameswari, Diyanti Ayu; Puspitasari, Aldita Cahyani; Firmaniar, Rizdyana; Ardiansyah, Moch Rizal (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Based on a preliminary study, it was found that there were still errors in reviewing prescriptions at Sumekar Hospital. Therefore, the researcher wanted to know the description of the completeness of the administration and pharmacy of doctor's prescriptions at the inpatient pharmacy installation of Sumekar Hospital. Method: This study is a descriptive study with a qualitative method. The data collection technique was carried out by evaluating existing prescriptions, from January to June 2022 and conducting in-depth interviews with the person in charge of the Head of the Pharmacy Installation of Sumekar Hospital. Data Collection Instrument In this study, the main instrument was an in-depth interview guideline. Results: From these data, it can be seen that the criteria that do not meet the prescription requirements or do not comply with Permenkes No. 72 of 2016 are the first patient's height, the second patient's telephone number, the third patient's age and the fourth patient's weight which must be on the prescription at Sumekar Hospital in order to meet the requirements specified in Permenkes No. 72 of 2016. From the pharmaceutical data, it can be seen that the criteria that do not meet the prescription requirements or do not comply with Permenkes No. 72 of 2016, namely the first is the drug dosage, the second is the strength of the preparation, and the third is the form of the preparation that must be on the prescription at RSU Sumekar in order to meet the requirements specified in Permekes No. 72 of 2016. Conclusion: After the researcher conducted an administrative and pharmaceutical study, it can be concluded that the prescription at RSU Sumekar does not meet the prescription requirements or does not comply with Permenkes No. 72 of 2016. meets the criteria or does not meet the requirements of the Minister of Health Regulation Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. Because there are still several criteria that do not meet the specified standards.